JASLARDÍ RUWXÍY TÁRBIYALAWDA ShAŃARAQ HÁM MILLIY ÚRP-ÁDET, QÁDIRIYATLARDÍŃ XÍZMETI - Dosxodjaeva, A. (SCIENCE and SOCIETY, 2025)
In the article, it is said that spirituality is an internal spiritual factor that represents the main essence of a person and gives a positive meaning and direction to his activity. Thoughts about the role of the family in the society, spiritual and moral education were expressed.